DETERMINANTS OF INNOVATION STRATEGY ON BUSINESS PERFORMANCE WITH COMPETITIVENESS AS AN INTERVENING VARIABLE IN BATIK MSMES IN EAST JAVA - Muhajir, Ali; Sukesi; Tampubolon, Liosten Rianna Roosida Ully (International Journal Multidisciplinary (IJMI), 2026)
Objective: The purpose of this study was to examine; (1) the effect of product innovation, process innovation, technological innovation, organizational innovation and service innovation partially on competitiveness (2) the effect of competitiveness on business performance (3) the effect of product innovation, process innovation, technological innovation, organizational innovation and service innovation partially on business performance (4) the effect of product innovation, process innovation, technological innovation, organizational innovation and service innovation partially on business performance through competitiveness in Batik MSMEs in East Java. Methods: The data processing method in this study used Statistical Package for the Social Sciences (SPSS) software version 27 and path analysis with Structural Equation Modeling (SEM) modeling PLS program version 4.00. The population in this study was 657 Batik MSME owners in East Java, with the calculation of the Slovin formula found as many as 249 samples. Results: The results showed that; (1) product innovation, process innovation, technological innovation, organizational innovation and service innovation partially have a positive and significant effect on competitiveness (2) competitiveness has a positive and significant effect on business performance (3) product innovation, process innovation, technological innovation, organizational innovation and service innovation partially have a positive and significant effect on business performance (4) product innovation, process innovation, technological innovation, organizational innovation and service innovation partially have a positive and significant effect on business performance through competitiveness in Batik MSMEs in East Java. Novelty: The novelty in this study lies in the use of the Digital Maturity Index as a new indicator in measuring business performance.